Asketisme Semar: Pergumulan Agama-Sosial - Muhammad Sungaidi (Refleksi, 2019)
Since prehistoric times ethnic and Javanese communities have been a religious and godly society. The divine value, monotheism, which is embedded in the spirit of Javanese people can be seen from cultural values, for example Wayang. Wayang as a medium for the cultivation of the divine spirit and social-society values cannot be separated from Wali Songo’s ingenuity, especially Sunan Kalijaga. Cultural values will be more easily accepted by the public if their delivery is subtle, persuasive and in accordance with the psychology of ethnic (Javanese) who prioritize subtlety of mind and taste. Some wayang figures who are quite familiar, favorite and have sacred value are Semar. Semar became the main character in everything, both as an ordinary figure and a role as a servant, state adviser and spiritual figure. In the wayang narrated that Semar always soothes and water the hearts of every human heart that is barren, restless, and far from God.